In service of two masters: the missionaries of Ocopa, indigenous resistance, and Spanish governance in Bourbon Peru - Jones, Cameron D. (Stanford University Press, 2018)
Introduction -- The birth of Ocopa (1709-1742) -- Rebellion, religion, and reform -- In the aftermath of rebellion -- "In service of both majesties": 1759-1784 -- The bullet or the bayonet -- From apogee to collapse -- Conclusion -- Appendix: important individuals to the events described -- Bibliography